2011
DOI: 10.1097/anc.0b013e318225a30c
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Infant Feeding Method on Neonatal Abstinence Scores of Methadone-Exposed Infants

Abstract: Breastfeeding may offer enhanced benefits for infants who have been exposed to methadone in utero. As such, in the absence of contraindications, mothers in methadone maintenance programs should be encouraged and supported to breastfeed their infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 30 publications
0
56
0
6
Order By: Relevance
“…However, two studies in infants exposed to opioids in utero showed that breastfed infants developed less PNA compared to formula fed infants 95,96. The previously mentioned observational study of our research group concluded that breastfeeding is protective for PNA in 247 infants exposed to SSRIs, mirtazapine or venlafaxine in utero.…”
Section: Influential Factorsmentioning
confidence: 60%
“…However, two studies in infants exposed to opioids in utero showed that breastfed infants developed less PNA compared to formula fed infants 95,96. The previously mentioned observational study of our research group concluded that breastfeeding is protective for PNA in 247 infants exposed to SSRIs, mirtazapine or venlafaxine in utero.…”
Section: Influential Factorsmentioning
confidence: 60%
“…Methadone levels are very low in breast milk and in infants who are breast-fed. Those results were replicated in a retrospective study of 28 infants, 57 where the NAS scores in breast-fed infants were significantly lower than the scores with formula and combination feedings. In 2006, Abdel-Latif and colleagues 56 reported in their study of 190 infants that breast-feeding decreased the length of treatment of NAS.…”
Section: Feedingmentioning
confidence: 75%
“…Though the amount of opiate being transferred in breast milk is very slight, [43] the possibility of breast milk opiate reducing severity of NAS has been suggested by studies showing that breast milk-fed infants have lower NAS scores than formula-fed infants. [44] …”
Section: Discussionmentioning
confidence: 99%